Effectiveness of Social Cognitive Theory–Based Oral Cancer Awareness Module Among Adolescents: An Interventional Study - Tejaswini B. Darukaradhya; Shwetha Kanyaloor Mallikarjuna; Pushpanjali Krishnappa; Anju James (Health Promotion Practice, 2026)
Oral cancer remains a significant public health challenge, particularly in India, where it accounts for a substantial global burden. Despite its preventability, awareness levels among adolescents remain low. Schools provide an ideal platform for health education interventions, yet traditional approaches often fail to yield lasting behavioural change. This study aimed to evaluate the effectiveness of a social cognitive theory (SCT)-based oral cancer awareness module in enhancing adolescents’ knowledge and self-efficacy. A cluster-randomized controlled trial was conducted between June and October 2017 in two high schools in Kaiwara, Karnataka. Adolescents aged 13–16 years ( N = 524) were randomly assigned to an SCT-based intervention group or a control group receiving conventional education. The intervention, delivered by trained teachers and peer leaders, incorporated interactive teaching tools such as flipcharts, videos, and PowerPoint presentations. Knowledge and self-efficacy were assessed at baseline, immediately post intervention, at 1 month, and 3 months using a validated questionnaire. The intervention group demonstrated a significant improvement in knowledge (baseline: 6.22 ± 2.4; 3 months: 12.93 ± 0.8) and self-efficacy (baseline: 4.48 ± 2.9; 3 months: 8.61 ± 1.3) compared to the control group ( p < .05). The role of teachers and peer leaders in reinforcement contributed to sustained learning. The SCT-based intervention was effective in enhancing oral cancer awareness among adolescents. Implementing theory-driven, school-based educational strategies can play a crucial role in long-term behaviour modification and cancer prevention.